2008
DOI: 10.3390/ijms9040498
|View full text |Cite
|
Sign up to set email alerts
|

Supported Phospholipid Bilayer Interaction with Components Found in Typical Room-Temperature Ionic Liquids – a QCM-D and AFM Study

Abstract: Quartz crystal microbalance with dissipation (QCM-D) monitoring and atomic force microscopy (AFM) were combined to evaluate the defects created by an ionic liquid anion and a cation in a supported phospholipid bilayer composed of zwitterionic lipids on a silica surface. The cation 1-octyl-3-methyl imidazolium (OMIM + ) was shown to remove lipids from the bilayer, increase the roughness to approximately 2.8 nm (~0.2 for stable supported bilayer) and possibly redeposit lipids with entrapped water. The anion bis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 39 publications
4
37
0
Order By: Relevance
“…Phase imaging was also employed to confirm the lamellar phases in the top leaflet, as the phase lag of the tip relative to the excitation signal is sensitive to surface properties, such as adhesion and viscoelasticity. Fig.2A (phase image) clearly demonstrates a large phase contrast (∼1 • ) between the two domains, which is interpreted as a change in bilayer softness (Evans, 2008;Leonenko et al, 2000), and thus confirms the proposed lamellar phases on the top leaflet of the DMPC bilayer.…”
Section: Cyp 2c9 Reconstitutionsupporting
confidence: 64%
“…Phase imaging was also employed to confirm the lamellar phases in the top leaflet, as the phase lag of the tip relative to the excitation signal is sensitive to surface properties, such as adhesion and viscoelasticity. Fig.2A (phase image) clearly demonstrates a large phase contrast (∼1 • ) between the two domains, which is interpreted as a change in bilayer softness (Evans, 2008;Leonenko et al, 2000), and thus confirms the proposed lamellar phases on the top leaflet of the DMPC bilayer.…”
Section: Cyp 2c9 Reconstitutionsupporting
confidence: 64%
“…8, Panel B and C [61,62]. At CMC (100 mM) the size of the vesicles increases largely and the BMOP forms a film around the gramicidin vesicle, this type of behaviour of the pyrrolidinium based IL with vesicles has been reported earlier [23]. The above results signify that the membrane bound gramicidin in its channel form have strong interactions with BMOP and well supported by the above discussed results.…”
Section: Fesem Characterizationsupporting
confidence: 81%
“…In depth investigation, computational as well as experimental studies of the interaction between ILs having different alkyl chain length and varied head groups with phospholipid membranes have been reported and the results showed disruption of the phospholipid bilayer at higher concentration of ILs with long hydrocarbon side chain [22][23][24]. Some recent findings also reported that ILs has the ability to fuse and aggregate lipid vesicles depending upon the length of the alkyl chain at higher concentrations [25,26].…”
Section: Introductionmentioning
confidence: 90%
“…Evans showed that imidazolium-based ILs with longer hydrocarbon tails more significantly destabilize liposomes and supported lipid bilayers [21][22][23]. Jeong et al also showed that longer ILs at higher concentrations more effectively insert into membranes, which induces membrane instability, leading to the lower transition temperature of membranes [24].…”
Section: Introductionmentioning
confidence: 96%